Cognitive focus affects spatial decisions under conditions of uncertainty - Tenbrink, Thora (Cogn Process, 2020)
Finding one’s way to a destination is a common, everyday task that often relies on spatial information provided by humans and/or automatic devices. However, the information can be inaccurate. How we decide which route to take will depend on our thoughts about the available route information, including who or what provided it, and how these sources may be associated with differential accuracy and fallibility. In three experiments (previously reported in Brunyé et al. (Q J Exper Psychol 68(3):585–607, 2015)), we found that when route directions conflicted with the perceived environment, people trusted the landmark information other humans provided, but relied on the turn direction information from an automatic device. But what guides these behavioral results? Here we present a systematic linguistic analysis of retrospective reports that sheds some light on how information about the direction source affects cognitive focus. A focus on direction sources in the instruction triggered a cognitive focus on the direction source throughout. Participants who systematically switched strategies focused more on features of the scenario than those who did not. Non-switching strategies were associated with a higher focus on the participants’ own reasoning processes, in particular when relying on turn information. These results highlight how cognitive focus is guided by scenario factors and individual preferences, triggering inferences that influence decisions.